Feasibility and Safety of Whole-Body Electromyostimulation in Frail Older People—A Pilot Trial - Bloeckl, Joerg; Raps, Sebastian; Weineck, Michael; Kob, Robert; Bertsch, Thomas; Kemmler, Wolfgang; Schoene, Daniel (Frontiers in Physiology, 2022)
Whole-body electromyostimulation (WB-EMS) induces high-intense stimuli to skeletal muscles with low strain on joints and the autonomic nervous system and may thus be suitable for frail, older people. However, if trained at very high intensities, WB-EMS may damage muscles and kidneys (rhabdomyolysis). This study aimed at investigating the feasibility, safety and preliminary efficacy of WB-EMS in frail, older people. Seven frail (81.3±3.5years), 11 robust (79.5±3.6years), 10 young (29.1±6.4years) participants completed an eight-week WB-EMS training (week 1-4: 1x/week; week 5-8: 1.5x/week) consisting of functional exercises addressing lower extremity strength and balance. Feasibility was assessed using recruitment, adherence, retention, and dropout rates. The satisfaction with WB-EMS was measured using the Physical Activity Enjoyment Scale for older adults (PACES-8). In week 1, 3 and 8 creatine kinase (CK) was assessed immediately before, 48 and 72 hours after WB-EMS. Symptoms of rhabdomyolysis (muscle pain, muscle weakness, myoglobinuria) and adverse events were recorded. Functional capacity was assessed at baseline and after eight weeks using the Short Physical Performance Battery (SPPB), Timed Up-and-Go Test (TUG), Choice Stepping Reaction Time Test (CSRT), 30-second Chair-Stand Test (30-STS), maximum isometric leg strength and handgrip strength. The recruitment rate of frail individuals was 46.2%, adherence 88.3% and the dropout rate 16.7%. All groups indicated a high satisfaction with WB-EMS. CK activity was more pronounced in young individuals with significant changes over time. Within older people CK increased borderline-significantly in the frail group from baseline-week 1 but not afterwards. In robust individuals CK increased significantly from baseline-week 1 and 3. No participant reached CK elevations close to the threshold of ≥5000 U/l and no symptoms of rhabdomyolysis were observed. With the exception of the TUG (p=0.173), frail individuals improved in all tests of functional capacity. Compared to the young and robust groups, frail individuals showed the greater improvements in the SPPB, handgrip strength, maximum isokinetic hip-/knee extension and flexion strength. WB-EMS is feasible for frail older people. There were no clinical signs of exertional rhabdomyolysis. WB-EMS proved to be sufficiently intense to induce meaningful changes in functional capacity with frail individuals showing greater improvements for several measures. Trial registry: clinicaltrials.gov (NCT04495647)